PROTOTYPE MONITORING AND CONTROL OF MINIATURE STEAM POWER PLANTS (PLTU) USING THE IOT-BASED FUZZY LOGIC METHOD - Sulatin, Moch. Dani Urdhy; Kustori, Kustori; Julaihah, Siti (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
This study develops a prototype monitoring and control system for a miniature Steam Power Plant (PLTU) using Fuzzy Logic based on the Internet of Things (IoT). The prototype manages operational variables such as voltage and current with a Fuzzy Logic algorithm, enabling adaptive control that enhances efficiency and stability. The integration of IoT via the Virtuino platform provides real-time supervision through mobile devices or computers, facilitating operators in monitoring and taking quick actions, and includes early notifications to detect anomalies. Test results demonstrate high accuracy in monitoring and control with automatic adjustments based on sensor data. Fuzzy Logic effectively addresses sensor data uncertainties, showing potential for application in full-scale PLTUs and industrial automation.